2005
DOI: 10.1016/j.jacc.2005.05.034
|View full text |Cite|
|
Sign up to set email alerts
|

Bifurcation Coronary Lesions Treated With the “Crush” Technique

Abstract: In the majority of bifurcation lesions treated with the crush technique, the smallest minimum stent area appeared at the SB ostium. This may contribute to a higher restenosis rate at this location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(129 citation statements)
references
References 12 publications
6
115
1
7
Order By: Relevance
“…Two-stent deployment may increase the risk of stent thrombosis and repeat revascularization in bifurcation LMCA lesions. 24,25) In our study, as shown in the Kaplan-Meier survival curve (Figure 1), most deaths occurred before 1 year after index PCI. If very late stent thrombosis had occurred more frequently in our study, the rates of MACE may have revealed different results.…”
Section: Discussionsupporting
confidence: 58%
“…Two-stent deployment may increase the risk of stent thrombosis and repeat revascularization in bifurcation LMCA lesions. 24,25) In our study, as shown in the Kaplan-Meier survival curve (Figure 1), most deaths occurred before 1 year after index PCI. If very late stent thrombosis had occurred more frequently in our study, the rates of MACE may have revealed different results.…”
Section: Discussionsupporting
confidence: 58%
“…6,7,18 Because bifurcation lesions vary and are complicated subsets of coronary artery disease, sophisticated imaging modality such as IVUS might be helpful to evaluate accurately and select more optimal treatment strategies. Previous studies using bare metal stent showed that IVUS guidance during PCI reduced the rate of in-stent restenosis and the incidence of reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…It may play an advantageous role to guide appropriate treatment strategy and affect the better clinical outcomes by optimal stenting for different individual cases. 2,6,7 Previous studies with bare metal stent and DES have shown that IVUS guidance during percutaneous coronary intervention (PCI) improved clinical outcomes. 8,9 However, the impact of IVUS on clinical outcomes has been controversial according to different lesion subsets.…”
mentioning
confidence: 99%
“…21 In most catheterization laboratories, IVUS is not frequently used due to the associated cost, time and unproven benefit for routine procedures, but a more liberal approach is suggested in patients with ambiguous lesions on coronary angiography or undergoing complex interventions to improve diagnostic accuracy and guide therapy to improve clinical outcomes. 15,16,22 …”
Section: Discussionmentioning
confidence: 99%